Eksplorasi Profil Kompetensi Mahasiswa pada Mata Kuliah Pengantar Pendidikan melalui Pembelajaran Mode Hybrid Berbasis Pemanfaatan Artikel Ilmiah - Hikmawati Hikmawati; Fathurrahman Fathurrahman (Kappa Journal, 2026)
This study aimed to explore students' competency profiles in the Introduction to Education course through hybrid learning based on the utilization of scientific articles. The study employed a quantitative descriptive approach and was conducted during the odd semester of the 2025/2026 Academic Year in the Physics Education Study Program, Faculty of Teacher Training and Education, University of Mataram. The research subjects consisted of 26 students enrolled in the Introduction to Education course taught by the researcher. The data were collected from the assessment of classroom discussion activities and individual assignments conducted through the SPADA UNRAM learning platform. Competency assessment covered nine indicators, namely content understanding, academic argumentation, utilization of scientific references in discussions, participation in discussions, accuracy of assignment content, depth of analysis, utilization of scientific references in assignments, critical thinking skills, and academic writing organization and language use. The data were analyzed using descriptive statistics, including mean, median, mode, standard deviation, frequency, and percentage. The results showed that students' competencies were categorized as high, with an average score of 86.73. All competency indicators were also categorized as high, with mean scores ranging from 85.9 to 87.4. A total of 50.00% of students were categorized as having high competency, 46.15% as very high, and 3.85% as moderate. These findings indicate that hybrid learning based on the utilization of scientific articles can effectively support the development of students' academic competencies, particularly in terms of conceptual understanding, academic argumentation, scientific literacy, and critical thinking skills.